Propriedades químicas das fases T e B da nióbia: uma investigação in silico - Mirele Bastos Pinto (2018)
Niobium pentoxide (Nb2O5), also known as niobia, exists in many polymorphic forms depending on the temperature, pressure, starting materials and techniques. This work reports the computational simulation using the Functional Density Theory (DFT) of the polymorphic phases T and B of the niobia, which are classified as low and medium temperature phases, respectively. A bulk study was performed for the two phases and in this study the structural, electronic, mechanical and bonding properties of the bulks and surfaces are elucidated by bulk modulus, projected density of states (PDOS), Bader topological analysis (QTAIM) and electron localization function (ELF). Niobia has interesting characteristics in the scope of the catalysis, because it presents acid sites that confer the high acidity material and some of the Lewis acid sites are not deactivated in the presence of water. In order to investigate reactivity, we chose B phase and performed a surface study because the literature does not report the preferential cleavage plane of any of the polymorphic phases of the niobia. The study showed that the (010)-2 cleavage plane present lowest formation energy and exposes niobium and oxygen atoms. Concerning the water adsorption on the surface, the molecular form is the most favorable, however, it is possible that the H + and OH- species of dissociative adsorption also can be present, because the calculations of the adsorption energies show that it is only 4.5 kcal mol-1 less stable than molecular adsorption. In addition, due to the oxidation potential of niobium compounds, adsorption of hydrogen peroxide on the (010)-2 surface was also investigated. The adsorption energies calculations indicate that the dissociative form and can be found to a greater extent on the (010)-2 surface, however the molecular (H2O2) and dissociative forms ( ) also may be present on the surface. Finally, the mechanism of isomerization of fructose glucose on the (010) -2 was investigated. The isomerization mechanism is divided into threesteps: opening of the glucopyranose ring following by an intramolecular C2 to C1 Hshift and fructofuranose ring closure. The reaction energy diagrams for glucose to frutose conversion showed that the step of intramolecular C2 to C1 H-shift, usually considered the most difficult step in this mechanism, is favorable in the presence of the surface (010)-2.